PENGEMBANGAN GAME EDUKASI UNTUK MENINGKATKAN NILAI AGAMA DAN MORAL ANAK USIA DINI DI TK AISYIYAH IKAN BANYAK KABUPATEN LIMA PULUH KOTA - Netri Winda; Delfi Eliza (Jurnal Educhild : Pendidikan dan Sosial, 2022)
This study aims to develop educational games to increase the religious and moral values of early childhood. The method used is Research and Development (R&D) with a 4-D model. This research was conducted in the Kindergarten at Aisyiyah Ikan banyak kabupaten lima puluh kot. In this study, the stages of validation, practicality and effectiveness were carried out. The results of the validity test obtained an average of 82.34% while the practicality test of the teacher's response reached 92.33℅ and 90.48℅ for observation of children's learning, testing the effectiveness of learning activities reached 88.4088 and the effectiveness of children's learning outcomes 81.01℅ Based on these results, educational games to improve the religious and moral values of early childhood developed can be used and practically applied in Kindergarten